What is the case for teaching with cases in evaluation?. Issue 172 (24th February 2022) - Linfield, Kenneth J.; Tovey, Tiffany L. S.
Abstract: This article introduces the volume on Case‐Centered Teaching and Learning in Evaluation by presenting the general rationale for using cases as a part of instruction in evaluation and essential points about how cases can be used as a part of teaching and learning about evaluation. This volume is the product of "The Case Collaborative, " an ongoing partnership among the authors and additional participants. In this introductory article, we tell the story of how this partnership developed, the goals and objectives identified by the group, and the primary concepts and strategies involved in case‐centered evaluation teaching and learning. We introduce our working definition of cases and share the critical connection of this work to purposeful reflection on our practice as evaluation practitioners and teachers. This theme of reflective practice in our work is introduced here and threaded throughout the remainder of the NDE volume.